Physiology of paluma guava plants fertilized with potassium and calcium - Cavalcante, Alian Cássio Pereira; Cavalcante, Lourival Ferreira; Cavalcante, Adailza Guilherme [UNESP]; Bertino, Antonio Michael Pereira [UNESP]; Bertino, Antonio Missiemario Pereira; Y Nubia, Marisa Ferreira (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2018)
Guava is a perennial fruit, highly preferred by the Brazilian consumer and in increasing commercial exploitation in almost all the national territory. The most required nutrients are nitrogen, followed by potassium and calcium with great participation in the growth and physiology of guava. The objective of this study was to evaluate the effects of potassium doses in the soil without and with calcium in the physiology of Paluma guava plants. The experiment was carried out in a randomized complete block design in a 5 × 2 factorial arrangement, with K 2 O of 0, 45, 90, 135 and 180 g plant -1 year -1 , without and with 120 g plant -1 year -1 calcium from calcium nitrate. The variables analyzed were chlorophyll indices (a, b and total), chlorophyll fluorescence and gas exchange. The results were submitted to analysis of variance by the “F” test and the potassium doses were submitted to regression analysis, using SAS © software version 9.3. Guava plants fertilized with only potassium in the soil had higher photosynthetic rate, water use efficiency and instantaneous carboxylation efficiency. The addition of calcium and potassium to the soil increased chlorophyll a, b, total, variable fluorescence, maximum fluorescence, quantum efficiency, stomatal conductance, transpiration rate and internal carbon concentration in guava.
Fisiología en plantas de guayaba paluma fertilizadas con calcio y potasio
Keywords: Chlorophyll; Physiological aspects; Psidium guajava